(untitled) (Research, Society and Development, 2021)
The National Policy for Permanent Education in Health (EPS) has structured the training of human resources for the Brazilian Unified Health System (SUS), presenting among its guidelines the adoption of active learning methodologies (MAs) to promote meaningful and critical education. This research, based on the systematic integrative review, aimed to deepen and systematize knowledge about the use of MAs strategies in EPS processes. The literature review involved the databases of the Virtual Health Library and obtained 18 papers. For data analysis, a synthesis matrix was used, in order to organize and categorize the information. We observed that all research focused on detailing the principles about MAs. Regarding the definitions, most of the works conceptualized MAs as an alternative method to the traditional teaching model. Among the implementation strategies, we list the work in groups, teams and actions in networks; the experimentation and problematization of reality; seminars, dialogues, dynamics and workshops. With regard to evaluations, the need for most inclusive and procedural practices is emphasized. In relation to integrated curricular guidelines, the importance of curricular bases that promote cohesion between knowledge and alignment of theory to practice is highlighted. Concerning the use of ICTs, we observed that this tool provides new ways of applying distance education and MAs. Finally, studies are suggested to delimit the concept of MAs with greater precision and depth, including innovative strategies that are applicable, replicable and transforming reality.